Pendekatan Efektif dalam Pengelolaan Sumber Daya Manusia di Lembaga Pendidikan Islam - Aulia Gusli, Ramadhoni; Sesmiarni, Zulfani; Akhyar, Muaddyl; Mira Lestari, Kurnia (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This research is motivated by technological developments and educational institutions must further improve their human resource management. Human Resource Management plays an important role in improving the quality of institutional education, especially Madrasah Aliyah Negeri (MAN). Researchers used descriptive qualitative methodology and the type of research was a case study in the field. To optimize the results, the researchers collected data through observations, interviews, and analysis of relevant documents. The research findings show that human resource management plays an important role in MAN 1 Pariaman City. This is evident from the significant beneficial effects resulting from its implementation. In addition, human resource management at MAN 1 Kota Pariaman is conducted through the application of various management functions, including planning, procurement, construction and development, promotion and transfer, dismissal, compensation, and staff evaluation. MAN 1 Pariaman City implements many strategies to improve human resource productivity. These strategies include providing continuous training and development programs, offering incentives and rewards, and ensuring proper construction and monitoring.